FEASIBILITY STUDY OF HYDROPOWER PLANT PROJECT BY COMPANY XYZ - Hansel B.M. Nababan, Rihuel
Indonesia's population continues to increase every year. This increase happens alongside the rising demand for electricity. On the other hand, the transition towards new renewable energy is being strongly promoted by both the Indonesian government and international bodies. This situation has prompted company XYZ, which operates in the procurement sector for the government, state-owned enterprises, and private companies, to expand their business in the utilities industry. In addition to the business aspect, company XYZ also wants to actively assist in the Indonesian government's programs. This study was conducted to perform a feasibility study on a hydropower plant project to be undertaken by company XYZ.